COACHING FOR START-UP MANAGERS IN IMPROVING TEAM INNOVATION - Dhimas Fachri Aziza (Universitas Airlangga, 2023)
The development of digital technology and information has triggered companies to have new ways of running their business. Technological advances make business activities easier, more efficient and effective. Companies must have a strategy that is capable of innovation and transformation in running their business and developing their human resources. There are several industrial sectors affected by the Covid-19 pandemic, one of which is the tourism industry. The number of foreign tourist visits to Indonesia in January 2021 was recorded to have decreased by 89.05 percent compared to January 2020, namely from 1.29 million visits to 141.26 thousand visits. Therefore, companies need leaders who are able to provide encouragement and motivation so that their members can continue to innovate amidst difficult situations. With coaching, managers can also facilitate self-learning, personal growth and how to improve performance using several interventions.